2011
DOI: 10.1111/j.1467-8373.2011.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Peacebuilding, gender and policing in Solomon Islands

Abstract: UN Security Council Resolution 1325 calls for a gender perspective to be integrated into the resolution of conflicts. This responsibility manifests itself in a number of more specific proposals, some easily assessable, others less so. In this paper, we begin by considering the success of the Regional Assistance Mission to Solomon Islands (RAMSI) – the poster child for peacebuilding efforts – at meeting these specific proposals. In light of this, we then go on to suggest ways in which RAMSI might meet greater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…Research from a range of policing and peacebuilding missions has shown that there is more of a chance of police officers encouraging others to cooperate if the police involved have an understanding of the local context (Dinnen et al 2006;Goldsmith and Dinnen 2007;Goldsmith and Harris 2009;McLeod 2009;Greener et al 2011). NZPOL Six argued that an understanding of the domestic context comes from police officers spending time getting used to the local situation by listening and observing.…”
Section: Collaborative Relationships and Task-oriented Masculinitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Research from a range of policing and peacebuilding missions has shown that there is more of a chance of police officers encouraging others to cooperate if the police involved have an understanding of the local context (Dinnen et al 2006;Goldsmith and Dinnen 2007;Goldsmith and Harris 2009;McLeod 2009;Greener et al 2011). NZPOL Six argued that an understanding of the domestic context comes from police officers spending time getting used to the local situation by listening and observing.…”
Section: Collaborative Relationships and Task-oriented Masculinitiesmentioning
confidence: 97%
“…Despite a growing literature examining broad issues related to gender and international policing, there is little evidence to support or refute this claim. Instead, the majority of literature on gender and international policing focuses on either gender mainstreaming within UNPOL (Olsson 2000;UNDPKO 2004UNDPKO , 2008UNIFEM 2007), the marginalization of women in UNPOL and local police forces (Olsson 2000;Fitzsimmons 2005;Greener et al 2011), or the absence of focus on masculinities in gender policy (Bendix 2009;Mobekk 2009;Myrttinen 2009b). In particular, there is a lack of understanding of what types of masculinities are valued within police institutions operating as part of UN police reform projects and whether the police do indeed represent a less militarized and less hypermasculine institution.…”
mentioning
confidence: 98%
“…Ten of these officers were directly involved in the programme while the remainder were expected to display the practices and principals of community policing in their work (Emmott, Barcham et al 2010). Around 17% of New Zealand Police officers deployed on overseas missions are female (Greener, Fish et al 2011), so it can be assumed that while the programme was being carried out, around 17% of those involved were female. While the CPPP was partly funded by the New Zealand Agency for International Development (NZAID) which has a gender mainstreaming strategy, there were no provisions within the programme for dealing with gender issues (Emmott, Barcham et al 2010:i).…”
Section: The Community Policing Pilot Programme and The Merging Of Security And Developmentmentioning
confidence: 99%
“…According to the literature on police reform, a key determining factor in the success of police reform programmes is the extent to which the foreign police are able to build respectful and equitable relationships with the host country police force. Better relationships are developed when police engaged in police reform prioritise learning about the local culture of the country in which they are stationed (Goldsmith and Harris 2009;McLeod 2009;Greener, Fish et al 2011). Also key is that police officers approach reform from the position of letting the local police, communities, leaders and organisations identify reform priorities, which is something rarely done (see for example Dinnen, McLeod et al 2006;Goldsmith and Dinnen 2007;McLeod 2009).…”
Section: Building Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation